Gambling harm prevention and harm reduction in online environments: a call for action - Virve Marionneau; Heidi Ruohio; Nina Karlsson (BMC, 2023)
Abstract Background Gambling is increasingly offered and consumed in online and mobile environments. The digitalisation of the gambling industry poses new challenges on harm prevention and harm reduction. The digital environment differs from traditional, land-based gambling environments. It increases many risk-factors in gambling, including availability, ease-of-access, but also game characteristics such as speed and intensity. Furthermore, data collected on those gambling in digital environments makes gambling offer increasingly personalised and targeted. Main results This paper discusses how harm prevention and harm reduction efforts need to address gambling in online environments. We review existing literature on universal, selective, and indicated harm reduction and harm prevention efforts for online gambling and discuss ways forward. The discussion shows that there are several avenues forward for online gambling harm prevention and reduction at each of the universal, selective, and indicated levels. No measure is likely to be sufficient on its own and multi-modal as well as multi-level interventions are needed. Harm prevention and harm reduction measures online also differ from traditional land-based efforts. Online gambling providers utilise a variety of strategies to enable, market, and personalise their products using data and the wider online ecosystem. Conclusion We argue that these same tools and channels should also be used for preventive work to better prevent and reduce the public health harms caused by online gambling.